Peran Usaha Kecil dan Menengah (UKM) dalam Meningkatkan Kesejahteraan Masyarakat - Roy Syaifudin; Asep Shodiqin; Nase Nase (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
The economic problems felt by the lower class of society who then run Small and Medium Enterprises (SMEs) independently, and this in Indonesia is a phenomenon that has indicators of rapid growth. The purpose of this study is to find out how the role and results of the implementation of small and medium enterprises in order to improve community welfare. Qualitative research methods. As for the results obtained, the Role of Small and Medium Enterprises in Prospering the Economy of Village Communities, namely as a seller of Fried Chicken or you could say fried chicken, must be familiar to the Indonesian people. The results of the research show that there are several indicators of successful community development through Fried Chicken fast food, including: a) The emergence of public awareness in increasing and developing potential as fast food entrepreneurs, b) The community also gets increased income from the fast food sector, c) The number of enthusiasts to open this small and medium business by producing Fried Chicken fast food